Technological Innovations and Pedagogical Advancements in Basketball Skill Learning: A Systematic Review of High School Physical Education - Abady, Andy Nur; Patrick Willyam M Butar Butar, Patrick Willyam M Butar Butar; Longakit, Jet; Velorine Gordichev, Velorine Gordichev (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
Purpose of The Study. This systematic review investigates technological and pedagogical innovations in high school basketball skill education. The study evaluates theoretical frameworks, identifies effective strategies for varied learners, establishes a skill acquisition framework, and offers practical insights for educators and curriculum designers. Material and methods. The research employed a systematic review methodology adhering to the PRISMA framework. The study searched multiple academic databases, primarily SCOPUS, targeting English publications from 2015-2024. The search applied Boolean logic and controlled vocabulary to examine basketball skill learning, technological interventions, and educational methodologies. Inclusion criteria included peer-reviewed articles relevant to high school basketball skill development with technological or pedagogical innovations. The analysis concentrated on three analytical dimensions: technological interventions, pedagogical approaches, and performance metrics. Results. The systematic review indicated notable advancements in basketball skill acquisition influenced by technological and pedagogical innovations. Intelligent sensor technologies offer high precision in movement evaluation, while cognitive science integration fosters novel skill development avenues. Artificial intelligence and machine learning demonstrate significant improvements in tactical skills, with enhancements ranging from 9.655 to 13.989 through generative AI instructional models. Motion analysis technologies are essential advancements, notably improving free throw accuracy by up to 13%. These findings signify a transformative evolution in basketball training, where advanced technologies and cognitive methodologies are fundamentally reshaping athletes' skill acquisition processes, exceeding traditional training paradigms. Conclusions. The landscape of basketball skill learning is undergoing a profound transformation driven by technological innovation and advanced pedagogical approaches. The emerging paradigm suggests a move towards more personalized, technology-enhanced, and cognitively informed training strategies. While promising, significant research gaps remain, particularly in developing comprehensive, integrated approaches to basketball skill learning. The study emphasizes the need for robust longitudinal designs to definitively demonstrate the long-term efficacy of innovative teaching methods.